Eruptive squamous cell carcinoma in a patient treated with concomitant pembrolizumab and imiquimod. Issue 12 (9th October 2019) - Kanekura, Takuro; Arimura, Akiko; Kirishima, Mari; Tanimoto, Akihide
Abstract: Pembrolizumab, a humanized monoclonal antibody against programmed cell death 1, is used for various malignant neoplasms. Toll‐like receptor (TLR) agonists, specifically targeting the TLR9 subfamily (TLR7–9), are treatment options for solid tumors and hematological malignancies. We experienced a case of eruptive squamous cell carcinoma (SCC) in a patient treated concomitantly with pembrolizumab and imiquimod, a TLR7 agonist. A 75‐year‐old woman who was given a diagnosis of bladder cancer with lung metastasis received pembrolizumab for 3 months when she was referred to our department for the evaluation of skin rashes on her hands. Her skin lesions were diagnosed as well‐differentiated SCC and treated with topical imiquimod. Two months after the start of imiquimod, more than 10 reddish papules appeared on her hands. The histological diagnosis of a new plaque was the same as an earlier biopsy. We herein describe this case in detail and provide a published work review.